PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI PENGUNGSIAN AKIBAT PERUBAHAN IKLIM DI PAKISTAN TAHUN 2022-2023 - Hany, Dinda Alifah; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Pakistan is one of the most vulnerable countries due to the effects of climate change. The climate crisis in Pakistan reached its peak in 2022 with nationwide flooding that caused massive losses and damage and triggered a massive internal displacement of the population. Not only did the disaster affect the local population, but it also impacted refugees, particularly Afghan refugees who had long sought protection in Pakistan. UNHCR, as the UN agency with the primary mandate to protect displaced persons, played a strategic role in responding to this crisis. This research aims to analyze how UNHCR handled the displacement caused by the climate disaster in Pakistan in 2022-2023. This research utilized a descriptive qualitative method with data collection techniques through document analysis. Using Barnett and Finnemore's International Organizations Theory and a Constructivist approach at the group level, this research found that UNHCR plays an important role as an independent actor with the authority to develop programs to be implemented, coordinate with various parties, and address new issues relevant to its primary mandate. The research revealed UNHCR played a major role in implementing the Pakistan: 2022 Flood Response Plan in each sector and in enhancing the resilience of refugees and local populations to climate disasters through climate action programs. The success of UNHCR's role in addressing climate change-induced displacement in Pakistan is demonstrated by the program's high operational achievements, positive beneficiary reviews, and UNHCR's central role in bridging the needs of refugees, host communities, and the global climate agenda. Keywords: United Nations High Commissioner for Refugees, Climate Change, Displacement, Pakistan, Refugee.